2012
DOI: 10.1901/jaba.2012.45-143
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Effects of Contingent Food on High‐probability Behavior

Abstract: The delivery of food contingent on 10 s of consecutive toy engagement resulted in a decrease in engagement and a corresponding increase in other responses that had been previously reinforced with food. Similar effects were not observed when tokens exchangeable for the same food were delivered, suggesting that engagement was disrupted by the contingent provision of the food, which may have functioned as a discriminative stimulus that occasioned competing responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In addition, the combined intervention did not interfere with item engagement. From a clinical standpoint, the lack of interference with item engagement may be important given that some researchers have shown that using edible items as reinforcers may reduce engagement in appropriate behaviour (e.g., Frank-Crawford et al, 2012). By reducing engagement in mouthing in an individual with deafblindness using edible items, our results replicated those of previous studies conducted with individuals who did not have visual and auditory impairments (e.g., Simmons, Kliethermes, & Smith, 2003).…”
Section: Experimental Design and Proceduressupporting
confidence: 78%
“…In addition, the combined intervention did not interfere with item engagement. From a clinical standpoint, the lack of interference with item engagement may be important given that some researchers have shown that using edible items as reinforcers may reduce engagement in appropriate behaviour (e.g., Frank-Crawford et al, 2012). By reducing engagement in mouthing in an individual with deafblindness using edible items, our results replicated those of previous studies conducted with individuals who did not have visual and auditory impairments (e.g., Simmons, Kliethermes, & Smith, 2003).…”
Section: Experimental Design and Proceduressupporting
confidence: 78%
“…DRA using a positive reinforcer, such as food, has proven more effective (e.g., DeLeon et al, 2001;Lalli et al, 1999). However, other reinforcers, such as a break, are reportedly used more often by practitioners (Graff & Karsten, 2012) and there are a number of potential negative effects associated with the use of food (e.g., Frank-Crawford et al, 2012). Methods to increase the efficacy of the functional reinforcer, a break, in the treatment of escape-maintained problem behavior could have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the presence of the tokens evoked responding. Frank‐Crawford et al () showed that reinforcers can become discriminative for responding; thus, it is possible that the mere presence of the tokens evoked responding in this phase.…”
Section: Discussionmentioning
confidence: 99%